Microwave-assisted extraction (MAE) method for optimization of dates seed (Phoenix dactilifera) extraction - Vindhya Tri Widayanti; Dodyk Pranowo; Claudia Gadizza Perdani; Dewi Kurnia Sinta; Shafira Arini Sundari (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Dates (Phoenix dactylifera) is a palm-type plant that belongs to the Phoenix genus, which widely grows in the Middle East and South Africa.  The use of date seeds was still limited.  Dates seeds contain high amounts of nutrient and bioactive compounds, such as fiber, phenols, and antioxidants. The microwave-assisted extraction (MAE) method could increase the extract yields in a shorter time and reduces the solvent volume. This research aimed to evaluate the optimal extraction time and material: solvent (w/v)  ratio. The response surface methodology (RSM) with the Central Composite Design (CCD) experimental design with two factors of extraction time (5 - 7 minutes) and the material: solvent ratio (1:10 - 1:50 (w/v)) was employed in this study. The responses were antioxidant activity (IC50), total flavonoid, and density. The results show that the optimum solution was an extraction time of 5.451 minutes and the ratio of material: solvent of 1:10 (w/v). This treatment produced dates seed extract with antioxidant activity IC50 of 28.406 ppm, total flavonoid of 2544.951 mg QE/g, and density of  0.886 g/mL. The  verification of the center point  was antioxidant activity IC50 of 27.849 ppm (98.04%), total flavonoids of 2573.723 mg QE/g (98.87%), and density of  0.8889 g/mL (99.67%), respectively.